A-train : memoirs of a Tuskegee Airman - Dryden, Charles W. (Charles Walter) (Tuscaloosa, Ala. : University of Alabama Press, 1997)
How does a black American prepare for a career in a profession traditionally closed to blacks? And how does he or she cope with the frustrations and dangers that subsequent experiences generate? A-Train is the story of one of the black Americans who, during World War II, graduated from Tuskegee Army Flying School and served as a pilot in the 99th Pursuit Squadron. Charles W. Dryden has prepared an honest, fast-paced, balanced, vividly written, and very personal account of what it was like to be a black soldier, and specifically a pilot, during World War II and the Korean War. Colonel Dryden's book commands our attention because it is a balanced account by an insightful man who enlisted in a segregated army and retired from an integrated air force. Dryden's account is poignant in illuminating the hurt inflicted by racism on even the most successful black people. As a member of that elite group of those young pilots who fought for their country overseas while being denied civil liberties at home, Dryden presents an eloquent memoir of the experiences he has shared and the changes he has witnessed.
Chapter 11. Camelot! (February 1946-June 1949) Part II: After Desegregation; Chapter 12. Lonely Eagles (June 1949-July 1950); Chapter 13. Over There-Again! (July 1950-February 1953); Chapter 14. Sayonara! (February 1952-September 1957); Chapter 15. Guten Tag, West Germany (September 1957-May 1959); Chapter 16. Auf Wiedersehen! (May 1959-January 1962); Chapter 17. Twilight of a Lonely Eagle (January 1962-August 1962); 18. Contrails (Timeless); Epilogue; Glossary; Bibliography; Index.
Includes bibliographical references (page 409) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Dryden, Charles W; United States. -- Army Air Forces -- Biography; Dryden, Charles W; United States. -- Army Air Forces; United States. -- Army Air Forces -- Biography; World War, 1939-1945 -- Aerial operations, American; World War, 1939-1945 -- Participation, African American; World War, 1939-1945 -- Personal narratives, American; African American air pilots -- Biography; Tuskegee Army Air Field (Ala.); Pilotes d'aéronef noirs américains -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- Military -- World War II; African American air pilots; Military operations, Aerial -- American; Military participation -- African American; Alabama -- Tuskegee Army Air Field; African American air pilots -- Biography; World War, 1939-1945 -- Aerial operations; Tuskegee Army Air Field (Ala.); 1939 - 1945; Personal Narrative; Biographies; Personal narratives -- American; Personal narratives; Récits personnels